Naloxone provokes catecholamine release in phaeochromocytomas and paragangliomas. - Bouloux, P; Grossman, A; Besser, G (1986)
The effects of low- (2 mg) and high-dose (10 mg) intravenous naloxone administration on circulating plasma catecholamines in four patients with proven and two patients with suspected phaeochromocytomas have been evaluated. In three out of four patients with confirmed phaeochromocytomas or paragangliomas, 10 mg naloxone resulted in a marked rise (290-575%) in circulating noradrenaline; despite combined alpha and beta-adrenoceptor blockade, in two out of four cases systolic and diastolic pressures rose whilst pulse rate fell. No response was seen to 2 mg naloxone in any patient. No humoral or pressor response was obtained in the fourth patient, who may have been secreting maximal levels of plasma noradrenaline at the time of study. In the two patients with suspected phaeochromocytoma, there was no response to naloxone: further investigations failed to reveal a source of abnormal catecholamine secretion in these patients. It is concluded that naloxone represents a new pharmacological agent which can provoke catecholamine release in patients with phaeochromocytomas; in such patients, endogenous opioids may regulate catecholamine release either from the tumour itself or from the enhanced peripheral catecholamine stores.